IMPLENTASI KEBIJAKAN PENERIMAAN PESERTA DIDIK BARU DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA SAMARINDA - sukarni; Nur fitriyah; Sestuningsih (BEduManagers Journal : Borneo Educational Management and Research Journal, 2020)
One of the very important aspect in the Education is related to the enrollment of new students which has a very complex problems. To overcome all the problems, the District Head Office of the Education and Culture Kota Samarinda, published a policy on the new students enrollment, year 2016/2017 by using online system/model. This research Purposes are (1) to describe the implementation of the District Head Office of the Education and Culture Kota Samarinda for new students enrollment policy, year 2016/2017 for SMA level and (2) to know how the implementation of the District Head Office of the Education and Culture Kota Samarinda for new students enrollment policy, year 2016/2017 can be accepted by community. This research uses qualitative approach with the technique of data collection through indept interview, observation and the documentation study. The sources of the informations for this research are the school headmasters and new student parents/new students. The research findings are (1) according to the school headmasters (the policy implementors), year 2016/2017 that the new students enrollment policy can be implemented on the SMA levels, although there are some problems associated with the students non-academic achievements, disability/Environment Devolopment(ED)/PTK, and the school capacity and the stages of the registration path. While according to the new students’ parents/ new students, the new students enrollment policy, year 2016/2017 can be accepted with four notes, namely the problem of the non-academic students’ achievement, disability/ED/PTK, school capacity and the stages of the new students enrollment path; (2) related to the registration phase students’ non-academic achievements, disability /ED/PTK done before the regular /general path, causes many problems; (3) system/model of selection for students’ non-academic achievements, disability/ED/PTK based on the leves of the highest value of the National Examination results causes problems; and (4) the school capacity according to the policy implementors and new students’ parents/new students hope the government provides enought school capacity for the community; and (5) Headmasters always have their HP on and they are always at school.